Análise técnica e de custos do processamento e da identificação de toras de teca com sistema digital - Silva, Eudes dos Santos da (2019)
This paper aimed to analyse the technical and economic aspects for the stages of processing and insertion of barcode for teak logs’ identification (Tectonas grandis L. f.). Data were collected at Campina farm, Pirizal district, Nossa Senhora do Livramento municipality, Mato Grosso. Processing and teak logs’ identification stages have been assessed, with barcode. The processing stage is composed by the operations of trees cleaning, shaft measurement and logs’ sectioning. The logs’ identification stage is composed by labeling and barcode registering operations. The last stage is popularly called “chipagem” (to insert a chip onto the logs). The technical analysis consisted of time and movements studies, which it was possible to determine the stages of operational cycles’ time and interruptions for each operation. Cost analysis was based on operation costs survey, based on real and estimated values. Based on technical analysis results, an average productivity of 0.75m3 cc/cycle and average operational efficiency of 63.61%, for processing stage, was obtained, and an average productivity of 0.50 m3 cc/cycle and average operation efficiency of 63.25%, for the identification stage. Based on costs analyses, an average operation cost of 7.95R$/h was obtained, for the processing stage, and 5,84R$/h, for the logs identification stage with barcode. By means of productive chain analysis of teak logs, it was possible to have a comprehensive vision regarding operational procedures, as well as about what kind of products and subproducts of wood meet each market’s demands. The barcode, on the identification stage, allows gains, a posteriori, due to the ease and follow-up of the logs for a dossier throughout the productive chain, improving control over storage time and cargo disembarkation. Time and movement studies allowed to realize that there’s a need for more training of work teams, to improve operational efficiency of logs’ processing and identification. Also, it was verified a reduction on costs at processing and identification stages, by logs’ class. At the logs’ identification with barcode, the biggest costs were with clamps’ consumption and labels, at the labeling operation.